Al-‘Amm Al-Khash: A Study of General and Specific Verses - Channah Qotrunnada; Siti Sanah (al-Afkar, Journal For Islamic Studies, 2026)
The use of ‘Amm (general) and ‘Khas (specific) expressions in the texts of the Qur'an and Hadith, as well as the importance of interpretative principles in understanding Islamic law. The Qur'an was revealed as a guide for life, encouraging Muslims to use their intellect. However, the diversity of language styles and the Arabic language's nature as the language of revelation requires scholarly tools, including interpretative principles, to avoid errors in interpretation. The research methodology uses a qualitative approach based on library research, involving primary and secondary sources to analyze the differences in meaning between general expressions (‘Amm), which encompass multiple meanings without limitation, and specific expressions (‘Khas), which have particular meanings. The study results indicate that ‘Amm expressions can remain general, convey specific meanings, or undergo takhsis (restriction), while ‘Khas expressions are limited to a particular entity or attribute. This study provides in-depth insights into the significant influence of ‘Amm and ‘Khas expressions on understanding Sharia texts and establishing Islamic law.